CircSamd4: A novel biomarker for predicting vascular calcification - Zhou, Yuting; Liu, Yehong; Xuan, Shiyi; Jin, Tianhui; Chen, Ke; Wu, Zufei; Su, Wentao; Chen, Liang; Zong, Gangjun (Journal of clinical laboratory analysis, 2022)
Background Vascular calcification (VC) is usually associated with cardiovascular diseases (CVDs), which are one of the main causes of mortality in the world. This study aimed to analyze the expression of circular RNAs (circRNAs) in patients with VC and to evaluate biomarkers for the diagnosis of VC. Methods Calcified human aortic endothelial cells (HAECs) and the calcification in mouse aorta were detected by qRT‐PCR. Subsequently, this was verified in the plasma of patients with coronary artery calcification (CAC). The plasma of 40 patients in the control group and 31 patients in the calcified group were detected by quantitative reverse transcription polymerase chain reaction (qRT‐PCR) to detect the level of circSamd4a in the blood. The diagnostic value was evaluated by logistic regression analysis and the working characteristics of subjects. Results In the HAECs, the qRT‐PCR showed a significant decrease in the level of circSamd4a expression in the calcification group compared to the control group (p < 0.05). The calcified mouse aorta showed the same trend for circSamd4a expression, wherein the difference was statistically significant (p < 0.05); the expression of circSamd4a was significantly downregulated in the plasma of patients with VC (p < 0.01). The receiver operating characteristic (ROC) curves of circSamd4a in patients with VC and control group showed that the area under the curve (AUC) was 0.81 (95% CI: 0.707–0.913; p < 0.001). Conclusion CircSamd4a showed a stable downward trend in different specimens, and had significant advantages as a biomarker for diagnosis of VC. CircSamd4a of calcified mouse aorta, endothelial cells and coronary artery calcified population showed a downward trend, and there was a significant negative correlation between circSamd4a and calcification score.